2018
DOI: 10.1074/jbc.ra118.003661
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhimurium has three transketolase enzymes contributing to the pentose phosphate pathway

Abstract: The genus is responsible for many illnesses in humans and other vertebrate animals. We report here that serovar Typhimurium harbors three transketolases that support the non-oxidative branch of the pentose phosphate pathway. BLAST analysis identified two genes, _ and _, that together encode a putative transketolase (TktC) with 46-47% similarity to the known TktA and TktB isoforms. Assessing the mRNA and protein expression for each of the three transketolases, we determined that all are expressed in WT cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The role of these pathways in virulence of Gram-negative organisms is not completely clear, but work has shown that the PPP is activated during infection. For example, in Salmonella enterica, the KO of the transketolase enzymes within the PPP renders the resulting mutant avirulent in a mouse model (Shaw et al, 2018;Spaans et al, 2015). One potential explanation for this could be that the upregulation of these pathways shunts carbon intermediates toward LPS biosynthesis, a key virulence factor in Gram-negative bacteria (Stincone et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The role of these pathways in virulence of Gram-negative organisms is not completely clear, but work has shown that the PPP is activated during infection. For example, in Salmonella enterica, the KO of the transketolase enzymes within the PPP renders the resulting mutant avirulent in a mouse model (Shaw et al, 2018;Spaans et al, 2015). One potential explanation for this could be that the upregulation of these pathways shunts carbon intermediates toward LPS biosynthesis, a key virulence factor in Gram-negative bacteria (Stincone et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…At present, Salmonella enterica serovars are reported worldwide as the most common cause of human gastroenteritis associated with the consumption of contaminated foods. S. enterica is a very important food-borne bacteria that results in several public health troubles for humans and animals [ 7 ]. It is considered to be the second bacterial foodborne disease infecting humans.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were centrifuged at 12,000 g and 4 °C for 10 min to remove cell debris and protein concentration was determined using BCA assay with BSA as a standard (Thermo Fisher Scientific). TKT activity was analysed as described previously (76). Briefly, each enzymatic reactions were performed at a final volume of 100 µl containing 20 µl of supernatant, 50 mM Tris (pH 7.5), 0.24 mM MgCl 2 , 10 µM thiamine pyrophosphate, 0.5 mM NADH, 3 units of glycerol-3-phosphate dehydrogenase, 10 units of triosephosphate isomerase, 0.5mM D-xylulose-5-phosphate, and 0.5mM D-erythrose-4-phosphate (all reagents obtained from Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%